(untitled) (Indian Journal of Animal Production and Management, 2017)
A present investigation was carried out in Guntur district of Andhra Pradesh to collect the information regarding various body measurements of Nellore breed sheep as a measure of comparison between three divisions namely Tenali, Guntur and Macherla of Guntur district. Field data was collected from total of 1200 sheep of different age groups namely 0-3 month, 4-12 month, 2 teeth, 4 teeth, 6 teeth and full mouth animals. The Mean body length of male recorded was 45.69 ± 0.66, 67.13 ± 0.90, 74.04 ± 0.39, 76.54 ± 0.54, 77.32 ± 0.49 and 78.23 ± 0.47 cm for 0-3 month, 4-12 month, 2 teeth, 4 teeth, 6 teeth and full mouth animals respectively and the corresponding values for female sheep were 44.14 ± 0.80, 62.75 ± 0.60, 70.03 ± 0.37, 70.78 ± 0.41, 71.19 ± 0.36 and 70.29 ± 0.42 cm respectively. The Mean body height of male recorded in these age groups were found to be 50.71 ± 0.79, 69.14 ± 0.85, 77.15 ± 0.43, 81.09 ± 0.54, 83.47 ± 0.43 and 82.80 ± 0.43 cm and the corresponding values for females were 49.49 ± 1.13, 65.24 ± 0.59, 73.42 ± 0.31, 75.48 ± 0.38, 76.55 ± 0.44 and 77.97 ± 0.37 cm respectively. The mean heart girth in male in these age groups were recorded to be 52.01 ± 1.01, 70.86 ± 0.92, 81.60 ± 0.46, 85.64 ± 0.64, 89.97 ± 0.52 and 88.84 ± 0.60 cm respectively and in case of female heart girth was noted to b 48.82 ± 1.05, 67.28 ± 0.62, 77.02 ± 0.31, 79.36 ± 0.36, 81.86 ± 0.38 and 83.46 ± 0.63 cm respectively. The mean body weight of male sheep in Guntur district were 11.05 ± 0.55, 22.13 ± 0.77, 34.96 ± 0.50, 38.57 ± 0.50, 43.14 ± 0.33 and 44.56 ± 0.76 kg and the corresponding values for female sheep were 9.60 ± 0.64, 19.92 ± 0.55, 27.36 ± 0.22, 30.20 ± 0.39, 32.91 ± 0.28, 34.37 ± 0.36 kg for these age groups respectively. During present investigation male were found heavier (p<0.05) and longer (p<0.05) than female in all age groups. Similarly the heart girth (p<0.05) as well as height (p<0.05) at withers were also bigger in male than those of the female.